The Croods - Sanders, Chris (Christopher Michael); DeMicco, Kirk.; Belson, Kristine; Hartwell, Jane.; Cleese, John.; Stone, Emma, 1988-; Cage, Nicolas, 1965-; Reynolds, Ryan.; Keener, Catherine; Duke, Clark, 1985-; Leachman, Cloris; Thom, Randy; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2013)
A prehistoric comedy adventure that follows the world's first family as they embark on a journey of a lifetime when the cave that's always shielded them from danger is destroyed. Traveling across a spectacular landscape, the Croods discover an incredible new world filled with fantastic creatures, and their outlook's changed forever.
Keywords: Prehistoric peoples -- Drama; Stone age -- Drama; Hombre prehistórico -- Teatro; Edad de piedra -- Teatro; Feature films; Children's films; Animated films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities